Upper Hauterivian-upper Barremian planktonic foraminiferal assemblages from the Arroyo Gilico section (southern Spain) - Silva, Isabella Premoli; Soldan, Dario Marcello; Petrizzo, Maria Rose (Journal of Foraminiferal Research, 2018)
Late Hauterivian-earliest late Barremian planktonic foraminifera from the Arroyo Gilico section (Subbetic domain, Betic Cordillera) have been investigated to correlate their distribution to ammonite zonation and calcareous nannofossil bioevents. The 72-m-thick section spans the interval between the upper Hauterivian ammonite Crioceratites hinelli Sub-zone, Crioceratites baleraris Zone and the lowermost upper Barremian ammonite Barrancyloceras barremense Subzone, Toxancyloceras vandenheckii Zone. Planktonic foraminiferal assemblages are rich and relatively diverse. At the base of the section in the C. binelli Subzone, as already known, Hedbergella sigali, H. infracretacea, H. daminiae, and Lil-liputianella semielongata are recorded. New findings include common Hedbergella praetrocoidea and H. aptiana along with rare specimens resembling H. excelsa based on their long and elevated spire. Early appearances of taxa continue up-section with the lowest occurrences (LOs) of H. ventriosa, then Lilliputianella eocretacea in the overlying Crioceratites krenkeli Subzone, followed by H. gorbachikae, while the LO of the 'clavate' Lilliputianella pauliani occurs just before the end of the Hauterivian within the topmost Pseudothurman-nia picteti Subzone. The lower Barremian is punctuated by a number of successive appearances, including the typical Glo-bigerinelloides blowi recorded in the upper lower Barremian Kotetishvilia compressissima Zone. The acme of the 'clavate' morphotypes occurs in the Moutoniceras moutonianum Zone across the Mid-Barremian Event (MBE); besides common L. semielongata, the taxa consistently present are L. pauliani with both typical and transitional morphologies, L. eocretacea, and to a minor extent "Globigerinelloides" sigali.